P0259PARAPROTEIN-RELATED RENAL LESIONS IN NEWLY DIAGNOSED MULTIPLE MYELOMA: CLINICAL AND PATHOLOGICAL CHARACTERISTIC OF 51 PATIENTS WITH KIDNEY BIOPSIES. (6th June 2020) - Lin, Zishan; Yu, Xiaojuan; Wang, Suxia; Cen, Xinan; Zhou, Fude; Zhao, Minghui
Abstract: Background and Aims: Renal involvement is common in multiple myeloma (MM). In this study, we examined kidney biopsy findings in patients with newly diagnosed MM (NDMM) and correlated them with clinical characteristics and survival. Method: Renal pathological findings were retrospectively studied in 56 patients with NDMM. Clinical and laboratory data as well as outcomes were collected from 51 patients with paraprotein-related renal lesions in NDMM. Patients were categorized according to the with or without myeloma cast nephropathy (MCN). Results: Among 56 patients with NDMM, 51 had paraprotein-related renal lesions, of which MCN was the most common lesion in 31 patients (60.8%), followed by amyloidosis in 12 patients (23.5%) and light chain deposition disease (LCDD) in 8 patients (15.7%). Five patients had nonparaprotein-associated lesions, of which minimal change disease was the most common diagnosis, seen in 3 patients (60%). Patients with MCN had significantly higher serum creatinine levels, a lower eGFR, a higher percentage of requiring dialysis at diagnosis, a higher incidence of progressing to end-stage renal disease (ESRD), lower hemoglobin levels, a lower percentage of albumin in urine protein, a higher level of serum albumin and were more likely to have a detectable M-spike but less likely to have a detectable monoclonal whole immunoglobulin than patients without MCN. Compared with patients with MCN, the median overall survival time of patients without MCN was significantly longer (not reached vs 39 months (95% CI: 9–69 months); P=0.047; Fig.1). According to the multivariate analysis, the independent predictors of overall survival were the number of myeloma casts (HR: 1.12, 95% CI: 1.07-1.25; P=0.014) and male sex (HR: 4.99, 95% CI: 1.36-18.38; P=0.016). Conclusion: Patients with MCN suffer from more serious and more urgent renal damage and can also present with high-grade albuminuria but without hypoalbuminemia. The number of myeloma casts and male sex are independent predictors of overall survival.